The impact of COVID-19 on Western Australian medical imaging clinical practice and workplace - Dann, Chloe; Sun, Zhonghua (Wiley-Blackwell, 2022)
Introduction: Medical imaging plays a key role in the management of patients with coronavirus disease-2019 (COVID-19). This field is at risk from the impacts of the pandemic on the practice and workplace of medical imaging professionals (MIPs). Recent research has explored this impact internationally and in various states of Australia; however, the impact of the pandemic on Western Australian (WA) MIPs is yet to be examined.